THE CONCEPT OF DIFFERENTIATED LEARNING: ELEMENTARY SCHOOL LEARNING DIVERSITY SOLUTION - Henry Aditia Rigianti (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This paper describes the concept of differentiated learning as a learning diversity solution in the classroom. Differentiated learning was launched simultaneously with independent learning (Merdeka Belajar), which has started to be implemented in elementary schools. The main feature of differentiated learning is to interpret every diversity possessed by students to be facilitated properly in learning activities. Differentiated learning refers to modifying the process of education and learning in the classroom to fulfill the learning needs of each student. Based on the implementation, the teacher must be able to consider that each student in the class has diverse and unique learning needs. Differentiated learning consists of the differentiation of content, processes, and learning products. Therefore, students must have broad opportunities to be able to demonstrate what they have learned in the learning process, which is carried out according to their learning needs. The research method used is literature review research. Data collection techniques are carried out by searching data through various sources, either papers, books, articles, or journals. The research results indicate that differentiated learning is considered to be able to facilitate the students’ diversity through a set of learning activities, which is based on the content, context, and product.